A case report: Dual-lead deep brain stimulation of the posterior subthalamic area and the thalamus was effective for Holmes tremor after unsuccessful focused ultrasound thalamotomy - Maesawa, Satoshi; Torii, Jun; Nakatsubo, Daisuke; Noda, Hiroshi; Mutoh, Manabu; Ito, Yoshiki; Ishizaki, Tomotaka; Tsuboi, Takashi; Suzuki, Masashi; Tanei, Takafumi; Katsuno, Masahisa; Saito, Ryuta (Frontiers in Human Neuroscience, 2022)
Holmes tremor is a symptomatic tremor that develops secondary to central nervous system disorders. Stereotactic neuromodulation is considered when the tremors are intractable. Targeting the ventral intermediate nucleus (Vim) is common; however, the outcome is often unsatisfactory, and the posterior subthalamic area (PSA) is expected as alternative target. In this study, we report the case of a patient with intractable Holmes tremor who underwent dual-lead deep brain stimulation (DBS) to stimulate multiple locations in the PSA and thalamus. The patient was a 77-year-old female who complained of severe tremor in her left upper extremity that developed one year after her right thalamic infarction. Vim-thalamotomy using focused ultrasound therapy (FUS) was initially performed but failed to control tremor. Subsequently, we performed DBS using two leads to stimulate four different structures. Accordingly, one lead was implanted with the aim of targeting the ventral oralis nucleus (Vo)/zona incerta (Zi), and the other with the aim of targeting the Vim/prelemniscal radiation (Raprl). Electrode stimulation revealed that Raprl and Zi had obvious effects. Postoperatively, the patient achieved good tremor control without any side effects, which was maintained for two years. Considering that she demonstrated resting, postural, and intention/action tremor, and Vim-thalamotomy by FUS was insufficient for tremor control, complicated pathogenesis was presumed in her symptoms including both the cerebellothalamic and the pallidothalamic pathways. Using the dual-lead DBS technique, we have more choices to adjust the stimulation at multiple sites, where different functional networks are connected. Intractable tremors, such as Holmes tremor, may have complicated pathology, therefore, modulating multiple pathological networks is necessary. We suggest that the dual-lead DBS (Vo/Raprl and Vim/Zi) presented here is safe, technically feasible, and possibly effective for the control of Holmes tremor.